The transition to sustainable living and practice - Leonard, Liam.; Barry, John, 1966- (Bingley, UK : Emerald, 2009)
"The Transition to Sustainable Living and Practice" provides a series of insights into real alternatives to the current economic malaise, with an examination of key themes such as transition towns, traditional villages, new green financial concepts, the sustainable utopia, co-operative farming, sustainability and activism, ecofeminism, green protectionism, intentional communities and a green philosophy of money.
The transition to sustainability: transition towns and sustainable communities / John Barry, Stephen Quilley -- Traditional living practices: return to the villages / Mark Somma -- Sustainable economics: a new financial architecture based on a global carbon standard / Molly Scott Cato -- Utopian sustainability: ecological utopianism / Marius de Geus -- Environmental exploitation: an analysis and taxonomy / Gerry Nagtzaam -- Ecological activism: sustainable living, activism and identity / Liam Leonard -- Ecofeminism: ecofeminism and the green public sphere / Chaone Mallory -- Sustainable planning: a green protectionism / Colin Hines -- Sustainability and the intentional community: green intentional communities/ Lucy Sargisson -- A green philosophy of money / Rupert Read.
Includes bibliographical references.
Description based on print version record.
Keywords: Sustainable living; Sustainable development; Sustainability; Social impact of environmental issues; Sustainability; Science -- Environmental Science; Business & Economics -- Environmental Economics